The university link and penitentiary system in the re-integration of people deprived of liberty in Baja California - Vázquez García, Joaquín; García, Luis; Zúñiga, Heidy (Omnia, 2024)
The connection between the Autonomous University of Baja California (UABC) and different sectors of society is common in the development of academic work, proposing monitoring of formulated programs and projects, in correspondence with the curricular guidelines in the degree of the Faculty of Human Sciences. La teaching represents a space and mechanism binding with the penitentiary system and the social reintegration of people deprived of liberty related to proven criminal causes. The academic training in the Faculty of Human Sciences in the degrees in Education Sciences, Psychology, Communication Sciences, Sociology, History and the Master’s Degree in Education (Area of ​​emphasis in Educational Management), recognize the value in credits in the study plans through inter-institutional academic linkge, and whose management is given from the academy with the purpose of linking, systematizing and defining the processes for the pertinent administration of the stays and evaluations of the students admitted to penitentiary centers.